Red Macroalgae Pyropia Columbina and Gracilaria Chilensis: Sustainable Feed Additive in the Salmo Salar Diet and the Evaluation of Potential Antiviral Activity Against Infectious Salmon Anemia Virus - Cortez-San Martin, M (Springer Netherlands, 2016)
Red macroalgae (Phylum Rhodophyta) are considered to be an important source of biologically active metabolites; their use as functional feed ingredients in fish diets can increase disease resistance and animal growth. Furthermore, red macroalgae can be cultured in a sustainable and environmentally friendly manner. We evaluate the potential antiviral activity against the infectious salmon anemia (ISA) virus of Chilean red macroalgae as a sustainable feed additive in the Atlantic salmon (Salmo salar) diet. Lyophilized Chilean red macroalgae concentrates were elaborated and added to a commercial diet. Diets were prepared with 0.1, 1.0, and 10.0 % of Gracilaria chilensis and Pyropia columbina separately, and 0.1 and 1.0 % of a mix of both species in a 1:1 ratio. The diets were fed to S. salar over a period of 2 months. We collected data on production parameters and blood samples. The serum and its constituents were challenged with the ISA virus in the presence of Atlantic salmon kidney cells and tested ex vivo for antiviral capacity using a plaque reduction neutralization assay. Fish fed a diet containing 10 % G. chilensis showed a significantly higher specific growth rate compared with fish fed the control diet. The feed conversion ratio was not significantly affected by treatments. Sera from fish fed the algae diets showed a significant increase in antiviral activity against the ISA virus compared with sera of fish fed the control diet that did not include red macroalgae. Diets including G. chilensis (1.0 and 10 %) exhibited the largest increase in antiviral activity. © 2015, Springer Science+Business Media Dordrecht.